Über das lineare System der Differenz-Differentialgleichungen mit ganzen Koeffizienten, die endliches Wachstum besitzen - Navickaitė, L. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Л. Навицкайте. О линейной системе дифференциально-разностных уравнений с целыми коэффициентами конечного порядка. III—IVL. Navickaitė. Diferencialinių-skirtuminių lygčių tiesinės sistemos su sveikais baigtinės eilės koeficientais klausimu